IT project management : on track from start to finish - Phillips, Joseph (Emeryville, California : McGraw Hill Education, 2002)
**CompTIA reviewed and approved, provides complete coverage of 2002 IT Project+ Certification exam objectives** Complete IT projects on time and within budget using the expert advice and valuable insight contained in this book. Find out how to best use your skills to keep your team motivated and address challenges--including changing business needs, budget restrictions, technical barriers, and even office politics. Contains handy worksheets and project files on the CD-ROM to help you practice what you$1 (Bve just learned.s
1. Starting the Project -- 2. Researching the Project -- 3. Working with management -- 4. Creating the budget -- 5. Creating a work breakdown structure -- 6. Organizing a project team -- 7. Building the project plan -- 8. Implementing the project plan -- 9. Revising the project plan -- 10. Enforcing quality -- 11. Managing teams -- 12. Completing the project -- A. CompTIA IT project+ exam objectives -- B. Working as an Independent Contractor.
Includes bibliographical references and index.
Keywords: PROJECT MANAGEMENT -- HANDBOOKS, MANUALS, ETC